1998
DOI: 10.5694/j.1326-5377.1998.tb139023.x
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disability among elderly people in the community

Abstract: ObjectivesTo determine the prevalence and determinants of disability among elderly people living in the community. DesignA cross‐sectional postal questionnaire survey. SettingNorthern Sydney Area Health Service. Participants1527 residents (622 men and 905 women) aged 65 years and over. Main outcome measuresSelf‐reported chronic illnesses, injuries or conditions; difficulties with activities of daily living assessed by the Health Assessment Questionnaire (HAQ); and home modification and use of functional aids. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 11 publications
1
39
0
5
Order By: Relevance
“…One of these was the World Mental Health Survey estimate from Ukraine as its reported 1 year prevalence of chronic back or neck pain of 42.2% was three SDs higher than the mean of 18 World Mental Health Survey estimates while the next highest estimate was 1.2 SD units above the mean 23. The other study removed was an Australian study which was a postal survey with low response rate, and had an undue upward effect on the region's estimates 24. This left a total of 218 estimates from 56 studies.…”
Section: Methodsmentioning
confidence: 99%
“…One of these was the World Mental Health Survey estimate from Ukraine as its reported 1 year prevalence of chronic back or neck pain of 42.2% was three SDs higher than the mean of 18 World Mental Health Survey estimates while the next highest estimate was 1.2 SD units above the mean 23. The other study removed was an Australian study which was a postal survey with low response rate, and had an undue upward effect on the region's estimates 24. This left a total of 218 estimates from 56 studies.…”
Section: Methodsmentioning
confidence: 99%
“…19 Em nossa amostra de pacientes com AR e idade média de 58 anos, a pontuação no HAQ de 1,1 é equivalente a de idosos de 85 anos. 18 20 Embora a literatura preconize uma alteração de 0,24 na pontuação do HAQ como clinicamente relevante, 21 reduç ões de 0,19; já podem ser referidas como uma melhora mínima na função. 20 A capacidade funcional medida pelo HAQ é influenciada não apenas pela idade ou pelo tempo de doença, mas também pelos níveis de dor e pelas medicaç ões em uso.…”
Section: Discussionunclassified
“…In fact, the EPM-ROM score is sensitive to the modification of functional status, translating the goniometry required to perform the basic activities of life. 17 Even in healthy individuals, there is loss of functional capacity throughout life; 18 and in RA patients, such a loss is more significant. 19 In our sample of RA patients with a mean age of 58 years, an HAQ score of 1.1 is equivalent to the score for people aged 85 years.…”
Section: Discussionmentioning
confidence: 99%
“…19 In our sample of RA patients with a mean age of 58 years, an HAQ score of 1.1 is equivalent to the score for people aged 85 years. 18 Sokka et al, assessing functional capacity in RA patients, established that HAQ values smaller than 1 would mean a milder disease, while values above 2 would suggest a severe illness. 12 The annual increase in HAQ score found by these authors was confirmed by Scott et al These authors found an annual increase of 1% in HAQ score.…”
Section: Discussionmentioning
confidence: 99%